Very, very, very dreadful : the influenza pandemic of 1918 - Marrin, Albert (Alfred A. Knopf, 2018)
Examines the flu pandemic of 1918 that killed millions of people worldwide. Highlights the history of plagues as well as the science involved in the transmission and impact of the influenza pandemic of 1918. Includes maps, archival photographs, and resources for further information.